Numerical investigations of biomass pyrolysis with partial oxidation in a drop tube reactor. (15th May 2023) - Bieniek, Artur; Jerzak, Wojciech; Gajek, Marcin; Magdziarz, Aneta
Abstract: This study relates to 2D numerical calculations of fast pyrolysis with partial oxidation of pine and pine bark in a drop-tube reactor at 550 °C. Numerical studies were supported by experiments using thermogravimetric analysis of pine, pine bark, and pure lignin. The study involved 3 atm of pyrolysis: pure nitrogen, 95% nitrogen/5% oxygen, and 90% nitrogen/10% oxygen v/v. Numerical calculations were performed using Euler–Lagrange multiphase theory. According to the results, it was possible to linearly reduce the amount of char from 49% to 34% for pine and from 57% to 36% for pine bark, as the oxygen content in the carrier gas increased from 0 to 10% v/v. Furthermore, the addition of oxygen decreased the required energy for pyrolysis from 1.55 to 1.1 MJ/kg for pine and from 1.6 to 1.1 MJ/kg for pine bark at the maximum considered oxygen content. Simultaneously, owing to the increasing oxygen content in the carrier gas, gaseous products were promoted, and the mass ratio of CO to CO2 was almost the same for all cases and was approximately 0.6. Graphical abstract: Image 1 Highlights: The model of biomass pyrolysis with partial oxidation was developed. Euler – Lagrange multiphase theory was involved in the simulations. Pyrolysis with partial oxidation reduced the amount of char and promoted gases. The addition of oxygen decreased the amount of heat required for pyrolysis. TG analysis confirmed the effects of pyrolysis with partial oxidation.